Some happy, others sad: exploring environmental justice in solid waste management in Kinshasa, The Democratic Republic of Congo. Issue 5 (4th May 2017) - Kubanza, Nzalalemba Serge; Das, Dillip Kumar; Simatele, Danny
ABSTRACT: This paper explores the concept of environmental justice (EJ) in solid waste management (SWM) in Kinshasa, the Democratic Republic of Congo (DRC). It evaluates the extent to which EJ occurs in SWM and discusses the factors accounting for this state of affairs. The paper examines the relevant theoretical framework(s) and mechanisms that would facilitate the attainment of EJ in Kinshasa. It is argued that solid waste (SW) often ends up in the poorest and least powerful communities in the cities of the DRC. A qualitative research methodology, which includes exhaustive critical review of the literature, system analysis, reflections from best practices through case studies and discussion with stakeholders, was used for this study. Findings revealed that SWM in Kinshasa is a duty entrusted to publicly-funded municipal authorities. There are evidences of a clear divide between the rich and poor neighbourhoods in the manner SW is managed. This is an inequality that has only recently begun to be recognised as injustice practices in SWM. It is argued that a politico-cultural mechanism on remedying SWM inequities could enable changes that will address EJ in Kinshasa. Such a solution will go directly against the prevailing notion "some happy, others sad".